To evaluate the efficacy of vaginal hysterectomy over abdominal hysterectomy among women with benign gynaecological diseases - a retrospective cohort study - Dulal Chandra Haldar; Suresh C Mondal; Soham C (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: This study was conducted to compare non-descent vaginal hysterectomy and abdominal hysterectomy with reference to, duration of operation, postoperative complications and postoperative ambulation. Methods: This is a retrospective cohort study for a period of two years April 2017 to March 2019 among 60 patients with uterine size of 14 weeks gestation who underwent vaginal (group V) and abdominal hysterectomy (group A). Data about preoperative, operative intervention as primary outcome variables and postoperative complications as secondary outcome variables was taken from hospital records. Frequency and proportions were calculated for quantitative variables and t test was used for comparison of categorical variables. Results: A total of 60 cases were selected and matched for age and parity. After statistical analysis with the collected data, it was seen that in group V operating time, blood loss, hospital stay, ambulation was found less and statistically significant (p value < 0.05) as compared to group A. The values are: mean operating time (94.4 vs 132.5 minutes), preoperative blood loss (201.17 vs 299.34 ml), hospital stay (5.87 vs 8.6 days), early ambulance (1.53 vs 2.5 days), early resume of sexual activities (39.9 vs 69.53 days). Conclusion: Non decent vaginal hysterectomy is a better alternative to abdominal hysterectomy in cases with uterine size <14 weeks.